2017
DOI: 10.1002/ccr3.997
|View full text |Cite
|
Sign up to set email alerts
|

Why could a woman have three Trisomy 21 pregnancies? – a case report

Abstract: Key Clinical MessageMosaicism, an important cause for recurrent T21, should be suspected in families with more than one affected child wishing to receive prenatal counseling. Fluorescence in‐situ hybridization analysis in a large number of cells and in different tissue samples is critical for detecting low‐level mosaicism and is a key prognostic factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…To date, many groups have reported that chromosomal aneuploidies were detected in the POCs in several cases with a history of RPL and normal karyotype of fibroblasts or lymphocyte genome. Their results revealed that maternal mosaicism most probably gives rise to embryonic chromosome aneuploidies [ 68 ], [ 69 ], [ 70 ], [ 71 ]. Recently, Ghevaria et al.…”
Section: Maternal and Paternal Genetic Factors Account For Rplmentioning
confidence: 99%
“…To date, many groups have reported that chromosomal aneuploidies were detected in the POCs in several cases with a history of RPL and normal karyotype of fibroblasts or lymphocyte genome. Their results revealed that maternal mosaicism most probably gives rise to embryonic chromosome aneuploidies [ 68 ], [ 69 ], [ 70 ], [ 71 ]. Recently, Ghevaria et al.…”
Section: Maternal and Paternal Genetic Factors Account For Rplmentioning
confidence: 99%
“…Cryptic mosaicism in the germ layer of the gonad has been proposed as one of the possible causes of unexplained chromosomal abnormalities in the fetus. Nevertheless, parental gonadal mosaicism should be considered when the karyotype is normal and a specific abnormality is recurrently observed[91][92][93]. It has been suggested that the genomic instability found in POC samples obtained from RPL families may be caused by genetic disorders that occur either during parental or at the postzygotic stage due to the function of the embryonic genome.…”
mentioning
confidence: 99%